To Save or not to Save the Kidney: Relieving Unilateral Obstruction May Significantly Improve an Initially Low Split Renal Creatinine Clearance - TİNAY, İLKER; TARCAN, TUFAN (GALENOS YAYINCILIK, 2016)
Objective The aim of this study was to evaluate the change in acute/subacute unilateral renal function after the relief of complete unilateral ureteral obstruction by nephrostomy. Materials and Methods Thirty patients were prospectively enrolled in the study. All had ureteral stone, which were located in the upper ureter in 24 (80%) and in the middle ureter in 6 (20%) patients. As all patients had high-grade hydronephrosis, a percutaneous nephrostomy catheter was placed for the relief of obstruction. At the first week of urinary diversion, 24-hour creatinine clearance (CC) of both affected and normal kidneys were evaluated. In order to determine the difference, same evaluation was performed on the fourth week of nephrostomy placement. Results The mean age of the patients was 44.6 (36-54) years. The mean CC of the affected kidney was 38.8 similar to 4.9 ml/min in the first week of urinary diversion and increased to 42.5 similar to 5.4 ml/min at the end of the fourth week (p<0.001). All patients showed an improvement in CC levels ranging between 2.3% and 17.3% with a mean rate of 8.5 similar to 4.7%. Conclusion According to our results, kidney function may improve during the first month after the relief of obstruction. This improvement may be significant for borderline renal function to determine the curative treatment of an obstructed kidney
Keywords: Creatinine clearance; nephrostomy; obstructive uropathy; URETEROPELVIC JUNCTION OBSTRUCTION; URINARY-TRACT OBSTRUCTION; URETERAL OBSTRUCTION; RECOVERABILITY; UROPATHY; PREDICTION; RECOVERY; REPAIR